Bio-Somatic-Power - Tucker, Ian (Outlines. Critical Practice Studies, 2011)
Biopower is a prominent force in mental health, with psychiatry having a strong influential grasp across the areas of definition of mental disorders, diagnosis, care, treatment, and legislation. One area that impacts upon the everyday lives of community mental health service users is treatment, largely dominated by medication. This paper will explore biopower in relation to the practices and management of mental health service users’ medication regimens. Michel Foucault’s insistence in his later work that power is the product of bodily forces will be drawn upon in highlighting the importance of undertaking analysis of medication regimens. Taking examples from a project focused on service user experience, the concept of ‘somatic enactment’ is suggested as a means through which to open up biopower to the localised concerns of service users with regard to the issue of managing one’s body on a day to day basis, as affected by medication. In doing so, the author seeks to move towards a notion of biopower that does not only work on a ‘top down’ manner, and in which processes of embodied subjectification can be illuminated, without recourse to a straightforward power-resistance framework.